Pertumbuhan & Perkembangan Seorang Anak dengan Kanker LCH, pada Usia Prasekolah (Suatu Tinjauan Studi Kasus) - Yuliana Hanaratri (Universitas Malahayati Lampung, 2024)
ABSTRACT In developing countries, survival rates in children with cancer are still far different from those in developed countries, and the condition of children with cancer and their treatment significantly impacts the growth and development of children and their families. Explore the achievement of growth and development of a child with cancer at preschool age who undergoes treatment to improve the quality of life of the child. Descriptive qualitative with case study approach. A child namely An., at preschool age is six years and three months old with Langerhans cell histiocytosis (LCH) cancer. The nutritional status category according to body weight to High, and BMI measurement is the good nutritional status (normal) with a Z-score with a threshold Z score (- 2 SD to + 1 SD). At the same time, in developmental achievement, there are some developmental delays in aspects of language development, and gross motor, while in the achievement of fine motor development are still several conditions that require attention